PENGARUH MODEL PEMBELAJARAN INKUIRI BERBANTUAN ALAT PERAGA PORUMPIN TERHADAP MINAT BELAJAR SISWA KELAS 2 SEKOLAH DASAR - Jannah, Desi Miftakhul; Malihatul Hawa, Anni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the differences and effects of implementing the inquiry learning model assisted by PORUMPIN teaching aids on the learning interest of second-grade elementary school students in multiplication material. This study was motivated by students’ low learning interest and the need for an instructional model that could increase student engagement in the learning process. The research employed a quantitative approach using a quasi-experimental design involving two groups: an experimental class and a control class. The participants consisted of 49 students, including 25 students in the experimental class and 24 students in the control class. Data were collected through learning-interest questionnaires, observations, pretests, and posttests. The data were analyzed using SPSS through descriptive statistics, Independent Sample t-Test, and Paired Sample t-Test. The findings revealed that the average learning-interest score of the experimental class was 80.32, which was higher than the control class average of 62.63. The statistical tests showed a significance value of 0.000 < 0.05, indicating significant differences and effects on students’ learning interest. Therefore, the inquiry learning model assisted by PORUMPIN teaching aids was proven to be effective in improving the learning interest of second-grade elementary school students.